A música de Lillian Fuchs para viola de arco no enfrentamento de hegemonias - Pavan, Fernanda Cristina (2020)
The domain of Cultural Studies approaches artistic manifestations in connection with the society where those arise from. Music is one of the founding elements of culture, and therefore it can be said that society is affected by music in its production of sense and meanings. Lilian Fuchs (1902 1995) was a musician, violist, interpret, teacher and composer, she faced two hegemo nic realities in he r work: the hegemony of the violin instrument that gained focus because of its high and bright pitch, that gave away the cultural impression that the viola was a second level instrument, and the hegemony of men as for the social invisibility that her wor k received in an acting space that still doesn't acknowledges thoroughly the production of women like Fuchs. From the deep dive into the life and work of Lilian Fuchs, with emphasis on the language of her compositions for viola in the XXth century and the exemplification drawn from her three didactic study books, this paper intends to build further knowledge into how the artist transferred to her work the necessities of the musical acting and sociocultural environments, besides the goal of disseminating and acknowledging the contribution of her work to the literature of viola modern pedagogy which justifies finally the academic and social relevance of this research.